Altered Immune Reconstitution in Allogeneic Stem Cell Transplant Recipients With Human Immunodeficiency Virus (HIV). (10th June 2020) - Murray, Daniel D; Zaunders, John; Milliken, Samuel T; Mee Ling Munier, C; Ford, Carole; Orla Morrissey, C; Visweswaran, Malini; Avery, Sharon; Sasadeusz, Joseph; Kwan, John; Desai, Shrinivas; Law, Matthew; et al.
Abstract: Background: Persons living with human immunodeficiency virus (HIV) are at elevated risk of developing the malignant diseases that require allogeneic stem cell transplantation (ASCT). Recent data suggest that these individuals are also at an elevated risk of certain complications post-ASCT. This risk may result from preexisting HIV-related factors affecting dynamics of immune reconstitution post-ASCT. However, to date, there has been little work describing the dynamics of immune reconstitution post-ASCT in persons with HIV and none comparing these data to controls without HIV. Methods: We assessed T-cell reconstitution in 6 ASCT with HIV recipients (HIV+ASCT) compared to a control population of 21 ASCT without HIV recipients. In a subset of HIV+ASCT recipients we performed additional flow cytometry profiling of CD8+ T-cell subsets and antigen specificity of reconstituting CD4+ and CD8+ T cells. Results: We observe no difference in post-ASCT CD4+ T cells between HIV+ASCT and HIV-negative ASCT recipients, despite much lower pre-ASCT CD4+ T-cell counts in the HIV+ASCT group. In contrast, we observed significantly higher CD8+ T-cell numbers in the HIV+ASCT group post-ASCT. The reconstituting CD8+ T-cells were predominantly CD45RO+, whereas homing markers and antigen specificity of these cells varied between participants. Conclusion: This study represents the most extensive characterization of immune-reconstitution post-ASCT in persons with HIV, and the first to our knowledge to compare these data to ASCT controls without HIV. The results indicate that immune reconstitution in this group can be affected by preexisting HIV infection and post-ASCT antigen exposure. Abstract : We describe T-cell reconstitution postallogeneic stem cell transplantation in 6 people with human immunodeficiency virus (HIV) compared to 21 controls without HIV. We observed a significantly elevated CD8+ T-cell expansion post-Allogeneic Stem Cell Transplant in recipients with HIV. The nature and specificity of the CD8+ T-cell population differed among individuals.